Employment Status and the Decision to Migrate - Schlottmann, Alan M.; Herzog, Henry W. (The Review of Economics and Statistics, 1981)
The purpose of this paper is to examine demographic and socioeconomic determinants of migration for both employed and unemployed. Hypotheses concerning effects of age education and public services are developed and tested using data on interstate migration of U.S. labor force from 1965 to 1970. For individuals at-risk to either primary or repeat migration age and education selectivity of migration were in general confirmed. However for unemployed potential primary migrants education selectivity was not observed. It was also found that the provision of welfare services have little or no impact on migration decision of unemployed....However unemployment was shown to significantly affect role played by educational quality and training accessibility within migration decision. (EXCERPT)